2022
DOI: 10.1097/j.jcrs.0000000000000909
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of a Scheimpflug tonometer to measure biomechanical parameters before and after myopic refractive surgery

Abstract: To assess the repeatability of several corneal biomechanical parameters with a Scheimpflug tonometer (Corvis ST) in myopic eyes and eyes that underwent transepithelial photorefractive keratectomy (transPRK), small-incision lenticule extraction (SMILE), or femtosecond laser-assisted in situ keratomileusis (FS-LASIK) surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…To our knowledge, this is the first prospective study that compares the new parameter CBI-LVC after SMILE applicating different cap thicknesses until now. CBI-LVC was shown to be of high sensitivity and specificity (sensitivity of 93.3% and specificity of 97.8% with a cut-off value of 0.2) for diagnosing post-LVC ectasia by distinguishing the stable corneas from the pathological ones [ 21 ], as well as good repeatability after SMILE [ 22 ]. Compared to CBI, CBI-LVC is targeted at patients after corneal refractive surgery and is not affected by corneal thickness, thus breaking through the obstacle of CBI in corneal biomechanical evaluation after laser corneal refractive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first prospective study that compares the new parameter CBI-LVC after SMILE applicating different cap thicknesses until now. CBI-LVC was shown to be of high sensitivity and specificity (sensitivity of 93.3% and specificity of 97.8% with a cut-off value of 0.2) for diagnosing post-LVC ectasia by distinguishing the stable corneas from the pathological ones [ 21 ], as well as good repeatability after SMILE [ 22 ]. Compared to CBI, CBI-LVC is targeted at patients after corneal refractive surgery and is not affected by corneal thickness, thus breaking through the obstacle of CBI in corneal biomechanical evaluation after laser corneal refractive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated the good repeatability of SSI in eyes of different CCT and in myopic eyes ( Wang et al, 2021 ; Lu et al, 2022 ). However, SSI values may differ among races ( Chua et al, 2017 ; Vinciguerra et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%